Integration Of The 21st Century Learning Skills (4c’s) Using Google Classroom: Developing Narrative Writing Skills Among Malaysian Upper Secondary School Students - Ramasamy, Raganeswari (2024)
This study discovers how upper secondary students at national secondary schools in Malaysia used the main 4C’s of 21st century learning skills which are communication, collaboration, critical thinking, and creativity thinking in developing narrative writing skills using an online learning platform via mobile learning. Therefore, this study was conducted in two secondary schools from two different states. A narrative writing module which was 4C’s to WRITE module was developed to practise narrative writing elements by using technology platform. It was a study which employed mixed-method data collections in this study. Teachers and parents were involved to examine the students’ activities when applying technology platforms to foster their narrative writing skills. The data were collected by using quantitative and qualitative instruments. For quantitative, the data collection method included pre-test and post-test, while the qualitative method involved participant observation, document analysis, focus group interview with the students, as well as semi-structured interview with the language teachers and parents.